Promoting regional tourism cooperation under CAREC 2030 a scoping study. - Lee, Junkyu; Asian Development Bank (Manila,Philippines Asian Development Bank, [2019])
It suggests this could be done through the identification of opportunities for enhancing and expanding cooperation among member countries in the tourism sector and by maximizing economic opportunities while safeguarding ecosystems. Promoting cooperation in the tourism sector is one of the operational priorities under the CAREC 2030 Strategy. Tourism is also recognized as an effective way of helping developing countries take part in the global economy and achieve the Sustainable Development Goals.
Keywords: Sustainable development; Economic development -- Central Asia; Asian Development Bank; Electronic book